Comprehensive analysis of endoscopic ultrasound (EUS) in mediastinal lesions: patient characteristics, diagnostic outcomes, safety, and efficacy: a multi-country study - Okasha, Hussein; Gadour, Eyad; Tayyab, Ghias Un Nabi; Seicean, Andrada; Hicham, Elbacha; Emad, Emad; Alamri, Turki; Tehami, Nadeem; Faraj, Heero Ismael; Alzamzamy, Ahmed; Hussein, Hiwa; Tag-Adeen, Mohammed; et al. (The Egyptian journal of internal medicine, 2025)
Background Mediastinal lesions are tumors that develop mainly from structures commonly located in the three compartments of the mediastinum and the paravertebral areas. The diagnosis of these lesions is primarily based on imaging studies such as computed tomography and magnetic resonance imaging, which confirm the presence of the lesions and suspected metastatic disease. The study aims to determine the factors that determine the diagnostic accuracy and yield of endoscopic ultrasound (EUS) in diagnosing mediastinal lesions. Methods This multi-country study involved a list of centers providing EUS services across ten countries—the United Kingdom, Algeria, Egypt, Iraq, Kingdom of Saudi Arabia (KSA), Lebanon, Morocco, Pakistan, Romania, and Thailand. The appropriate information was collected regarding EUS-FNA and EUS-FNB procedures, including needle types, nature of lesion, needle passes, and complications of the techniques. The frequency/percentage conveyed data on the qualitative variables. The p-values were obtained using the Chi-square two-tailed exact test. The significance of the analysis was defined as p < 0.05. All the syntheses were performed using the Statistical Package for the Social Sciences (SPSS version 27; SPSS Inc., Chicago, IL, USA). Results A total of 439 participants were involved in this study, 255 (58.1%) males and 184 (41.9%) females, with a mean age of 55.73 ± 14.93 years. EUS-FNA and EUS-FNB diagnostic yield was influenced by needle types, needle size, number of needle passes, and lesion size. Among females, 44.6% were diagnosed with EUS-FNA, 42.8% with EUS-FNB, and 50.0% with EUS-FNA and FNB. Conversely, 55.4% of males were diagnosed using EUS-FNA and 57.2% with EUS-FNB. The association between gender and the diagnostic method, however, was statistically insignificant ( p = 0.197). Needles with smaller diameters (22G) offered greater diagnostic yield than needles with larger diameters (19G). A minimal number of needle passes (between 2 and 4) showed a higher diagnostic yield than a higher number of needle passes (> 5). EUS-FNB accounted for a 0.5% complication incidence rate each for fever, pain, thoracic pain, and hemorrhage. EUS-FNA had no complication rate. Patients undergoing EUS-FNA, EUS-FNB, or both procedural examinations had no significant complications ( p = 0.085). Conclusion The diagnostic yield of EUS procedures is affected by needle types, number of needle passes, lesion size, and needle size. Besides, EUS-FNA and EUS-FNB are infrequently associated with various complication rates. These techniques are safe and offer higher diagnostic yield when utilized responsibly by endosonographers.